Pelatihan Keterampilan Pengemasan dan Uji Cita Rasa Cookies Kacang Ikan Gabus (Channa Striata) dalam Pencegahan Stunting pada Balita di Kelurahan Pelambuan Kota Banjarmasin - Widyarni, Ari; Netty, Netty; Inayah, Husnul Khatimatun; Ilmi, M. Bahrul; Fakhsiannor, Fakhsiannor; Lely Octaviana, Elsi Setiandari (Universitas Baiturrahim, 2025)
The results of the 2022 Indonesian Nutrition Status Study (SSGI) show that the stunting rate in Indonesia is 21.6%, South Kalimantan 24.6% and Banjarmasin City 22.4% (5). The city of Banjarmasin with several children under five as many as 64,785 people with a stunting incidence rate of 22.4%, although this figure is below the figure of Kalimantan Province (24.6%), but still above the national average (21.6%). Pelambuan is one of the villages located in West Banjarmasin District in Banjarmasin City, located in the working area of the Pelambuan Health Center with an area of 1.22 Km and a population of 28,715 people with several stunted children under five as many as 24. This activity was carried out on Sunday, May 5, 2024, at 10.00 WITA until it was completed which was carried out at the house of the head of the PKK cadre of Pelambuan Village, Banjarmasin City, with the target of PKK cadres and mothers under five as many as 17 people with the method; pretest, counseling, training, and posttest. This activity was carried out in several stages, namely preparation, and implementation which included packaging and taste testing of Snakehead Fish Nut Cookies (Channa Striata) to making packaging and determining the capital price and selling price. The results of this activity can be known from the 17 respondents who conducted a taste test, namely most of the respondents liked the taste, aroma, color, texture/crispiness, the appearance of cookies, and the appearance of the packaging. In addition to their consumption, it is recommended to be used as a business and sold to increase family income to increase turnover for partners engaged in the economic sector.